Combined bendamustine, prednisolone and thalidomide for refractory or relapsed multiple myeloma after autologous stem-cell transplantation or conventional chemotherapy: results of a Phase I clinical trial - Pönisch, Wolfram; Rozanski, Marta; Goldschmidt, Hartmut; Hoffmann, Franz Albert; Boldt, Thomas; Schwarzer, Andreas; Ritter, Ute; Rohrberg, Robert; Schwalbe, Elke; Uhlig, Jens; Zehrfeld, Thomas; Schirmer, Veronika; et al. (British journal of haematology, 2008)
Thalidomide is an effective agent for advanced refractory or relapsed multiple myeloma (MM), although dose-limiting toxicity (DLT) may limit its use. This Phase I study found that a combination of low-dose thalidomide with bendamustine and prednisolone (BPT) maintained or increased efficacy, whilst avoiding DLT in 28 patients with MM that was refractory or that had relapsed after conventional chemotherapy or high-dose therapy with stem-cell support. BPT comprised fixed doses of bendamustine (60 mg/m2) and prednisolone (100 mg), and escalating doses of thalidomide (50, 100, 200 mg). Treatment cycles were repeated every 28 d until the occurrence of maximum response, DLT, or disease progression. Twenty-four patients responded after at least two cycles (four complete remission, six very good partial remission, 14 partial remission). Median progression-free and overall survival for all patients was 11 and 19 months respectively. Only mild/moderate non-haematological side effects were observed and no patient developed dose-limiting haematotoxicity. Transient grade 3-4 neutropenia was reported in 12 patients, and grade 3-4 thrombocytopenia occurred in two patients. We conclude that BPT therapy was well tolerated in patients with relapsed or refractory MM, with a response rate higher than 80%. The maximum tolerated dose of thalidomide was not reached in this study.